The addition of vermicompost and biostarter affects the growth, total phenolic and antioxidant activity of Echinacea purpurea - LUTFIA FAJAR CHOIRUNNISA; YULI WIDIYASTUTI; SOLICHATUN SOLICHATUN; AHMAD YUNUS (Smujo International, 2022)
Abstract. Choirunnisa LF, Widiayastuti Y, Solichatun, Yunus A. 2022. The addition of vermicompost and biostarter affects the growth, total phenolic and antioxidant activity of Echinacea purpurea. Nusantara Bioscience 14: 148-154. Echinacea purpurea (L.) Moench or purple coneflower is a medical plant that originated in North America and contained various bioactive compounds, one of which is phenolic. Applying organic fertilizer like vermicompost has been reported to increase plants' bioactive compounds' components and antioxidant activity. The purpose of this study was to determine the addition of vermicompost and biostarter on the growth, total phenolic and antioxidant activity of E. purpurea. Split-Plot Randomized Complete Block Design was used with dosages of vermicompost 0, 40, 60, and 80 g/plant and different types of biostarter from Banana peel waste and effective microorganisms (EM). The results showed that treatment of 80 g/plant vermicomposts and EM highest resulted in the growth rate parameters (plant high, leaf numbers, leaf area, roots volume, plant fresh and dry weight) and total phenolic content with 1.802%. On the other hand, the herb extracts had the highest result with the treatment of 40 g/plant vermicomposts and EM (4.96%). The antioxidant activity was tested using the DPPH method with TLC and showed that all treatments indicated positive antioxidant activity.